Endoglin (CD105) and proliferation index in recurrent glioblastoma treated with anti-angiogenic therapy - Bastos, António G. P.; Carvalho, Bruno; Silva, Roberto; Leitão, Dina; Linhares, Paulo; Vaz, Rui; Lima, Jorge (Frontiers in Oncology, 2022)
Introduction CD105 is an angiogenic biomarker that is useful to determine the microvessel density (MVD) within a tumor, namely, in highly vascularized tumors like glioblastoma (GBM). However, its expression has shown inconsistent associations with the prognosis of GBM patients. The aim of this study was to evaluate the value of MVD-CD105 (microvessel density assessed with anti-CD105 antibody) and Ki-67 (proliferation index marker) as prognostic and therapy response biomarkers, specifically in primary tumors and in recurrent tumoral specimens of a cohort of GBM patients treated with bevacizumab upon recurrence. Materials and methods We conducted a retrospective study of 102 consecutive GBM patients treated with bevacizumab upon recurrence at CHUSJ between 2010 and 2017. Demographic, clinical, and survival data of all patients were collected and analyzed. The tissue expression of MVD-CD105 and Ki-67 in primary and recurrent specimens was correlated with progression-free survival after temozolomide (PFS-1), progression-free survival after bevacizumab (PFS-2), and overall survival (OS). Results The immunohistochemical expression score for MVD-CD105 was similar in primary and recurrent tumoral specimens (mean scores of 15 and 16, respectively). Likewise, the mean Ki-67 expression was similar in primary (mean of 31% of tumor cells) and recurrent tumoral specimens (mean of 29% of tumor cells). MVD-CD105 expression in primary tumors had no impact on PFS-1, PFS-2, or OS. At recurrence, patients whose tumors showed increased MVD-CD105 had worse median PFS-2 (2 vs. 8 months, p = 0.045) and OS (17 vs. 26 months, p = 0.007) compared to those whose tumors showed lower MVD-CD105. CD105 tumoral pattern and localization had no impact on prognosis. Ki-67 expression was not associated with differences in survival outcomes. Conclusion In this study, higher MVD-CD105 expression in recurrent GBM patients seems to be associated with a worse PFS-2 and OS while portending no prognostic significance in the primary tumors. This highlights the importance of keeping track of the molecular evolution of the tumor over the course of the disease.